Armchair Disagreement. (21st July 2017) - Weber, Marc Andree
Abstract: A commonly neglected feature of the so‐called Equal Weight View, according to which we should give our peers' opinions the same weight we give our own, is its prima facie incompatibility with the common picture of philosophy as an armchair activity: an intellectual effort to seek a priori knowledge. This view seems to imply that our beliefs are more likely to be true if we leave our armchair in order to find out whether there actually are peers who, by disagreeing with us, force us to revise our beliefs. This article argues that the Equal Weight View should be spelled out in such a way that not only actual peer disagreement requires us to revise our beliefs, but also merely possible peer disagreement. This result is not a reductio ad absurdum of the view. Quite the opposite: it shows that the view is, contrary to appearance, compatible with our common way of doing philosophy.